Assessing corrosion and scaling potential of drinking water samples: A case study of Chattogram water distribution network, Chattogram, Bangladesh (Journal of Bangladesh Academy of Sciences, 2025)
The consequences of corrosion and scaling potential in drinking water resources are susceptible to public health. In Chattogram, Bangladesh, the Chattogram Water Supply and Sewerage Authority (CWASA) is principally responsible for providing water and sanitation services. Here, 100 samples were collected to forecast the corrosive-scaling behaviors using five indices: Aggressiveness (AI), Puckorius (PSI), Larson-Skold (LS), Langlier (LSI), and Ryznar (RSI) were programed. The findings revealed that 100% of the samples had corrosive tendencies established on the values for LSI, RSI, and PSI; in contrast, the LS index indicated scaling tendency in 83% of the samples, and the remaining samples either showed corrosion or evidenced a high rate of corrosion. A range of artificial and natural sources of potential contamination were indicated by the statistical correlations and principal component analysis (PCA)To prevent problems with finances and health, water supply networks should take corrective action to remove corrosion and its by-products.J. Bangladesh Acad. Sci. 49(1); 87-102: June 2025